Surface Polarity-Insensitive Organosilicasome-Based Clustering of Nanoparticles with Intragap Distance Tunability - Yoon, Seokyoung; Lee, Byoungsang; Kim, Chansong; Chang, Jun Hyuk; Kim, Min Jeong; Bae, Hyung Bin; Lee, Kyung Eun; Bae, Wan Ki; Lee, Jung Heon (AMER CHEMICAL SOC, 2021)
The limited intragap distance tunability of clustering nanoparticles with different surface chemistries resulted in unwanted interference between embedded nanoparticles and restricted functionality. This leads to an urgent need for a new strategy that enables the assembly of building block nanoparticles obtained from solvents with different polarities in defined compositions, distances, and orientations. Herein, we used organosilicasome (OSS), an organic-inorganic hybrid compound covered with a surfactant, to cluster diverse nanoparticles with high configurational tunability regardless of their surface chemistry. OSS is capable of gluing building block nanoparticles and inducing their co-encapsulation. The dissolvable characteristics of OSS facilitate controlled dissolution of nanoclusters, allowing the adjustment of the gap distance between building block nanoparticles and resulting in closely packed and loosely packed nanoclusters. Owing to OSS's silica-based chemical nature, the synthesized nanoclusters can be silicified through simple addition of a silica precursor to have a robust mesoporous silica body. In consequence, OSS enables the synthesis of multifunctional nanoclusters, especially with enhanced fluorescence, by controlling the distance in long range between gold nanoparticles and quantum dots. These tunable and multifunctional nanoclusters, synthesized from OSS, should provide a new platform ranging from the exploration of interactions at the nanoscale to the advent of unconventional multifunctional nanomaterials.
Keywords: DYNAMIC LIGHT-SCATTERING; GOLD NANOPARTICLES; CHEMISTRY; NANORODS; BONDS